The Ratio of Income to Money Supply: An International Survey - Doblin, Ernest M. (The Review of Economics and Statistics, 1951)
While this article was in press, the Editors were shocked to learn of the death of Dr. Ernest M. Doblin on July I4. They take this opportunity to pay tribute to the important work which Dr. Doblin did in many fields of economics and especially in the area of national income. The availability of income statistics as well as their improvement owe a great deal to Dr. Doblin. The following article stands as it was printed from manuscript without the benefit of author's corrections in proof.